Psychosocial interventions to improve adherence in depressed and anxious older adults prescribed antidepressant pharmacotherapy: a scoping review - Sarah T. Stahl; Joelle Kincman; Jordan F. Karp; Marie Anne Gebara (SAGE Publishing, 2023)
Medication nonadherence in depressed and anxious older adults is prevalent and associated with non-response to antidepressant pharmacotherapy. Evidence-based options to improve medication adherence are limited in this population. To review the state of the literature on the types and efficacy of psychosocial interventions for improving antidepressant pharmacotherapy adherence in depressed and anxious older adults. We conducted a scoping review according to PRISMA-ScR guidelines. PubMed/Medline and article references starting in 1980 up to 28 February 2023 were reviewed. Of the 710 records screened, 4 psychosocial interventions were included in the review. All studies included depressed older adults, and none included anxious older adults. Samples included racial and ethnic minorities and were primarily women. The psychosocial interventions consisted mainly of psychoeducation with usual care as the control comparison. Measures of antidepressant adherence included self-reported adherence or pill counting. Three of the four randomized controlled trials improved medication adherence rates and reduced depression symptom burden. Effective interventions exist for improving antidepressant medication adherence in depressed older adults. Improved adherence can reduce depression symptom burden. The lack of interventions for anxious older adults highlights the need to develop and deliver interventions for anxious older adults prescribed antidepressant pharmacotherapy.